2021
DOI: 10.1002/chem.202100950
|View full text |Cite
|
Sign up to set email alerts
|

Steric Effects on the Thermal Processes of Hemithioindigo Based Molecular Motor Rotation

Abstract: Tuning the thermal behavior of light driven molecular motors is fundamentally important for their future rational design. In many molecular motors thermal ratcheting steps are comprised of helicity inversions, energetically stabilizing the initial photoproducts. In this work we investigated a series of five hemithioindigo (HTI) based molecular motors to reveal the influence of steric hindrance in close proximity to the rotation axle on this process. Applying a high yielding synthetic procedure, we synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 56 publications
1
13
0
2
Order By: Relevance
“…For this reason, an increase in rotation speed was observed with increasing substituent size. 136 Replacing the stereogenic methyl groups in the allylic position of first-generation HTI motor 37 with more sterically demanding ethyl groups in motor 38 was coupled with an acceleration of 10 ms. 135 A similar trend was observed in imine motors based on camphorquinone. It was found that the half-lives for the NI step decreased from 7.5 h to 10 min when moving from substitution of a cyclopropyl group in the motor to a larger t Bu group on the N atom (compare 23 and 33 ) indicating a ground state destabilisation of the metastable Z state with respect to the transition state.…”
Section: Rotation Speedsupporting
confidence: 62%
See 2 more Smart Citations
“…For this reason, an increase in rotation speed was observed with increasing substituent size. 136 Replacing the stereogenic methyl groups in the allylic position of first-generation HTI motor 37 with more sterically demanding ethyl groups in motor 38 was coupled with an acceleration of 10 ms. 135 A similar trend was observed in imine motors based on camphorquinone. It was found that the half-lives for the NI step decreased from 7.5 h to 10 min when moving from substitution of a cyclopropyl group in the motor to a larger t Bu group on the N atom (compare 23 and 33 ) indicating a ground state destabilisation of the metastable Z state with respect to the transition state.…”
Section: Rotation Speedsupporting
confidence: 62%
“… 133,134 On the other hand, introducing steric hindrance in the fjord region can be used as a tool to increase the THI barriers. 135 For the first-generation HTI motor 6 the highest thermal barrier (for the E M → E S conversion) was 13.1 kcal mol −1 , equating to a half-life of 662 μs. The thermal barrier for the Z M → Z S was calculated to be 5.5 kcal mol −1 ( t 1/2 = 1.5 ns), and for this reason the Z M isomer could not be observed empirically.…”
Section: Rotation Speedmentioning
confidence: 98%
See 1 more Smart Citation
“…They are, nevertheless, sufficient to capture the steric hindrance, which has been shown to be important in other contexts, such as lightdriven machines [39]. For these light-driven molecular motors, precise control over the sterics can both increase and decrease the motor's speed [40].…”
Section: Discussionmentioning
confidence: 99%
“…Extending the laser excitation wavelength to 445 nm for Z ‐DBTDs also consolidate its universal applicability, especially for bioorthogonal ligation via promotion of the cycloaddition rate. The millisecond lifetime of the “metastable” E ‐DBTDs with superior photophysical features make it an ideal T‐type photoswitch element for design of light‐driven reciprocating molecular engines in which fast‐response and energy conversion are essential [52] . The photo‐switching properties of DBChDs (Ch=O, S, Se, Te), e.g., t 1/2 and ring‐strained energy, can also be widely tuned by replacing chalcogen atom on the bridge, from an ultra‐short lifetime to one‐way photo‐conversion.…”
Section: Introductionmentioning
confidence: 99%